2003
DOI: 10.1053/jlts.2003.50024
|View full text |Cite
|
Sign up to set email alerts
|

Membrane barrier of a porcine hepatocyte bioartificial liver

Abstract: Pores in the membrane of a bioartificial liver (BAL) allow it to function as a semipermeable barrier between its contents (i.e., liver cells) and components of the recipient's immune system. This study is designed to assess the influence of pore size on immune response to a BAL containing porcine hepatocytes. Sixteen healthy dogs were divided into four groups (four dogs per group) based on pore size of the BAL membrane and level of exposure to porcine hepatocytes. Group 1 dogs were administered porcine hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…On the other hand, de novo donor-specific antibodies that develop after transplantation are capable of triggering insidious graft injury in the late phase of post-transplantation. Protection against hyperacute rejection and chronic rejection are vital to BAL systems [27,28], as well as to organ transplantation and to cell transplantation [29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, de novo donor-specific antibodies that develop after transplantation are capable of triggering insidious graft injury in the late phase of post-transplantation. Protection against hyperacute rejection and chronic rejection are vital to BAL systems [27,28], as well as to organ transplantation and to cell transplantation [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Mass transfer rates are mainly determined by membrane permeability [24,30]. Larger pore size enables more efficient exchange of substances via the membrane of the module [28]. Conversely, a membrane with a large pore size may permit permeation of immunoglobulins that can cause antibody-mediated rejection of embedded hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been in pre-clinical large animal models utilizing both hepatocyte-based devices [12,13] and whole-organ liver perfusion [14], as well as in limited clinical applications using porcine hepatocytes or whole livers [2,[15][16][17][18]. In our present report, we utilize a genetically modified GalTKO.hCD46 porcine liver designed to eliminate hyperacute rejection while simultaneously attempting to interfere with the constitutive activation between VWF and the GPIb receptor by administering D-arginine vasopressin (DDAVP) and αGPIb antibody.…”
Section: Introductionmentioning
confidence: 99%
“…In one report, liver failure patients developed a significant xenoreactive antibody response after exposure to pig hepatocytes in a BAL employing an apheresis membrane of 200 nm permeability (Baquerizo et al, 1999). Studies involving healthy animals have indicated that a membrane permeability of 150–400 kDa (~10–20 nm) served as an effective barrier to the patient's cytotoxic immune response against hepatocytes within the BAL (Nyberg et al, 2003, 2004). Less studied is the influence of the BAL's membrane permeability on mass transfer rate, detoxification, and removal of other waste products that accumulate in liver failure (Patzer, 2006).…”
Section: Introductionmentioning
confidence: 99%